Teledentistry as an alternative for dental care during the pandemic by COVID-19 - Revelo, Grace (2021)
Teledentistry emerged as an alternative to continue dental care during the COVID-19 pandemic due to the restriction of consultations to urgent care and dental emergencies. This scientific note offers an overview of the advantages, disadvantages, and recommendations for the application of teledentistry in professional practice.